ANALYSIS OF REASONS INCREASE CONCENTRATION OF IRON IN GROUNDWATER INTAKE IN SHEPETIVKA TOWN - Shevchenko, O.; Korneienko, S.; Dihtiaruk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The chemical composition of underground water sources was analyzed. It was found that most likely flow to the intake of iron in Shepetivka town Khmelnytsky region. That allowed to determine with sufficient certainty the forms host iron in groundwater and suggest the most appropriate deferrization technology.